INTERAKSI VORTEX DAN PEMBANGKITAN GAYA SAYAP KEPAK PADA KODISI TERBANG MELAYANG - NUGROHO (NIM: 23609301); Pembimbing : Dr. Lavi R. Zuhal, SETYO
Nowadays, Particle Image Velocimetry (PIV) system has been developed and implemented extensively in many different areas in any institution throughout the world. The remarkable performance of capturing the image of instantaneous flow field and transforming it into flow visualization has led many fluid mechanic scientists to understand the complex flow phenomena. This thesis study the relationship of the vorticity distribution with force generated by a flapping rigid plate was investigated with digital particle image velocimetry. Measurements were conducted under the hovering condition with a flapping rigid plate for the wing model. The thesis discusses some fundamental principles of flapping wing, Digital PIV system concern its developed technique which is using deformation window. Next, force determination was performed based on impuls equation and the result is compared with other reference and check the consistency with experiment result. The data acquisition was performed observing spanwise and chordwise view of the model to capture Leading Edge Vortex (LEV) and Tip Vortex (TV). At the spanwise view, the acquisition was performed at 50% of chord, otherwise at chordwise view the acquisition was performed at 90% of span. And then some thorough study about vortex interaction is performed based on experiment result to make some analysis about flow phenomena around flapping motion. The vortex interaction should be consistent with Helmholtz law of vorticity stated that vorticity is conserved in vortex tube. The experiment results show that the vortex is have role in force generation and consistent with the Helmholtz law.